The International Criminal Court: An Introduction - Novak, Andrew (Springer, 2015)
This book is about the International Criminal Court (ICC), a new and highly distinctive criminal justice institution with the ability to prosecute the highest-level government officials, including heads of state, even in countries that have not accepted its jurisdiction. The book explores the historical development of international criminal law and the formal legal structure created by the Rome Statute, against the background of the Court’s search for objectivity in a political global environment. The book reviews the operations of the Court in practice and the Court’s position in the power politics of the international system. It discusses and clarifies all stages of an international criminal proceeding from the opening of the investigation to sentencing, reparations, and final appeals in the context of its restorative justice mission. Making appropriate comparisons and contrasts between the international criminal justice system and domestic and national systems, the book fills a gap in international criminal justice study.